A preposition is something you can end a sentence with: Learning English stranded prepositions through structural priming. (April 2015) - Conroy, Mark A; Antón-Méndez, Inés
This study investigated whether second language (L2) learners of English could learn to produce stranded prepositions through structural priming. Structural priming is the tendency for speakers to repeat the structure of previously experienced sentences, without intention or conscious awareness of such behaviour, and is thought to be associated with implicit learning of syntactic structure. The syntactic structure chosen for this study was the stranded preposition in English relative clauses, a structure which is known to be difficult for L2 learners to acquire, and which is often replaced by a related ungrammatical interlanguage variant: null preposition (null prep). It was hypothesized that, during and just after a structural priming treatment, learners would produce more sentences containing stranded prepositions and fewer null prep sentences than before the treatment. The results revealed that learners indeed produced more stranded prepositions during and after priming than before and we interpret this behaviour as a possible indication of implicit learning of an L2 structure. However, learners did not produce significantly fewer null preps during and after priming than before. We discuss the findings in terms of second language acquisition theory, interlanguage processes, and possible pedagogical implications.